Enhance Removal Pollutant from Batik Industrial Wastewater via Photo- Fenton Process: Efficiency and Kinetic Study - Oki Setiawan; Siti Adriani; Haposan Vincentius Manalu; Aninditiya Amalia; Ifti Luthviana Dewi; Insan Kamil; Darti Purnama Sari; Popi Sasniati (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
The present research evaluates the efficiency of the Photo-Fenton-like process under UV irradiation by varying ratio of hydrogen peroxide (H₂O₂) to Chemical Oxygen Demand (COD) and H₂O₂ to ferrous ion (Fe²⁺) using wastewater from a batik manufacturer in Gresik. Initial experiments demonstrated that varying the ratio of H2O2/COD contributes to Chemical Oxygen Demand (COD) removal, while maintaining a constant H2O2/Fe2+ ratio. The result reveals a significant effect on Chemical Oxygen Demand (COD) removal achieving 64.58% efficiency which indicates that highly reactive OH* radicals successfully generated in photo-Fenton-like process. Further optimization by increasing the ratio H2O2/COD = 15 (g/g) and H2O2/Fe2+ = 20 (g/g) resulting on maximum percentage of Chemical Oxygen Demand (COD) removal of 92.47% proving the massive production of OH* radicals. The kinetics reaction model which describes the Chemical Oxygen Demand (COD) degradation rate showed the BMG kinetic model, with parameters of 1/m = 0.9352, 1/b = 0.7159, and a coefficient of determination (R²) of 0.9986, indicating an excellent fit and high predictive accuracy of the kinetic model for this process. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).